Caught in a bottleneck: Habitat loss for woolly mammoths in central North America and the ice‐free corridor during the last deglaciation. Issue 2 (16th December 2020) - Wang, Yue; Widga, Chris; Graham, Russell W.; McGuire, Jenny L.; Porter, Warren; Wårlind, David; Williams, John W.
Abstract: Aim: Identifying how climate change, habitat loss, and corridors interact to influence species survival or extinction is critical to understanding macro‐scale biodiversity dynamics under changing environments. In North America, the ice‐free corridor was the only major pathway for northward migration by megafaunal species during the last deglaciation. However, the timing and interplay among the late Quaternary megafaunal extinctions, climate change, habitat structure, and the opening and reforestation of the ice‐free corridor have been unclear. Location: North America. Time period: 15–10 ka. Major taxa studied: Woolly mammoth ( Mammuthus primigenius ). Methods: For central North America and the ice‐free corridor between 15 and 10 ka, we used a series of models and continental‐scale datasets to reconstruct habitat characteristics and assess habitat suitability. The models and datasets include biophysical and statistical niche models Niche Mapper and Maxent, downscaled climate simulations from CCSM3 SynTraCE, LPJ‐GUESS simulations of net primary productivity (NPP) and woody cover, and woody cover based upon fossil pollen from Neotoma. Results: The ice‐free corridor may have been of limited suitability for traversal by mammoths and other grazers due to persistently low productivity by herbaceous plants and quick reforestation after opening 14 ka. Simultaneously, rapid reforestation and decreased forage productivity may have led to declining habitat suitability in central North America. This was possibly amplified by a positive feedback loop driven by reduced herbivory pressures, as mammoth population decline led to the further loss of open habitat. Main conclusions: Declining habitat availability south of the Laurentide Ice Sheet and limited habitat availability in the ice‐free corridor were contributing factors in North American extinctions of woolly mammoths and other large grazers that likely operated synergistically with anthropogenic pressures. The role of habitat loss and attenuated corridor suitability for the woolly mammoth extinction reinforce the critical importance of protected habitat connectivity during changing climates, particularly for large vertebrates.